The Exploration of Character Values in Physics Learning on Momentum, Impulse, and Collision Materials - Astalini; Darmaji; Kurniawan, Dwi Agus; Oktavia, Sri Wina; Triani, Elza; Azzahra, Miftahul Zannah (Journal of Education Reseach and Evaluation, 2023)
Character education is everything the teacher does to influence the character of students. The teacher helps shape student behavior by giving examples, how to speak or deliver good material, and various other related things. This study aims to explore character values in physics learning in the materials of momentum, impulse, and collision. The method used is qualitative with a type of documentation study research. The instrument used by researchers is to collect books, both softbooks/hardbooks, as well as related literature. This research shows the results that in class X there are several characters that are not applied by students during the learning process, this is because in the learning process students are not directed to these character values, of course it will have a negative impact on students because it will affect the student learning process. as well as social moments in the student's environment. The research recommendation is that it is hoped that in the future the character values of students will be more refined so that they can build and produce a better generation. The urgency of this research is that during learning the teacher can add characters that are not yet in the teacher's book so that character education for students can fulfill character values.